Penerapan Pendekatan Pembelajaran Terpadu Model Keterhubungan Dalam Meningkatkan Hasil Belajar Peserta Didik Pada Konsep Perubahan Wujud Benda - Haryati Mahyudin (Peneliti.net, 2023)
This study aims to examine the application of an integrated learning approach to the connectedness model in improving student learning outcomes in the concept of changes in the shape of objects (a study in class IV of Al-Irsyad Elementary School, Ternate City). This type of research is descriptive while the research design is a single group pretest-posttest, which aims to find out 1) the application of the connectedness model can improve student learning outcomes in the concept of changes in the form of objects, 2) the effectiveness of the application of the connectedness model in improving student learning outcomes in the concept change in object shape. The population in this study totaled 20 students, while in this study the variables were student learning outcomes before learning denoted by X1 and student learning outcomes after learning with an integrated learning approach connectedness model denoted X2. The technique used to collect data in this study is by using a test technique. After analysis using the t-test statistic where there is thit > ttab or 6.14 <2.09 with a significant level of 5% with dk = 19, according to the test criteria then Ho is rejected. This shows that the application of the integrated learning approach to the connectedness model in improving the learning outcomes of fourth grade students at SD Al-Irsyad Ternate City, especially in the concept of changing the shape of objects between X1 and X2 is 11.6 or 25.26%.